Formulation and evaluation of fluconazole pro-niosomal gel for topical administration - Sandeep G, Vasavi Reddy D, Srinivas Reddy Devireddy (Journal of Applied Pharmaceutical Science, 2014)
The present investigation was aimed to explore the potential of proniosomal gel for the topical delivery of fluconazole. Fluconazole-loaded proniosomes were prepared by the coacervation method using different non-ionic surfactants (spans and tweens) and evaluated for various parameters like size, shape, stability, entrapment efficiency, in-vitro release, ex-vivo skin permeation and retention study. Results showed that proniosomes composed of span 20 (F1), span 60 (F4), span 80 (F7) were more stable compared with tween 20 (F10) and tween 80 (F13) with smaller size, “i.e.” 4.08±0.18 µm, 2.61±0.15 µm, 2.01±0.12 µm, 8.56 ± 0.20 µm, and 7.10 ± 0.31 µm, respectively, along with higher entrapment efficiency (approx. > 46 %). Ex-vivo skin penetration and retention studies revealed that cutaneous deposition was affected by the nature of surfactant and vesicle size. Therefore the proniosomes containing span 60 having high amount of drug retained in skin, i.e. 25.97 ± 1.28 which can help in localized delivery of drug especially in fungal mediated skin diseases, thereby increased efficacy for prolonged period can be achieved.
Keywords: Fluconazole, proniosomes, surfactants, topical delivery,skin.